Prarancangan Pabrik Sodium SilikatDari Pasir Silika Dan Natrium Hidroksida Kapasitas 65.000 Ton Per Tahun - Zarmica, Ade Juli; , M Mujiburrohman, S.T., M.T., Ph.D; , Rois Fatoni, S.T., M.Sc., Ph.D (2016)
Sodium silicate plant with raw materials of sodium hydroxide and silica sand, is planned to be established in the industrial area of Gresik with a capacity of 65,000 tons/year. In the process of producing sodium silicate is performed using continueous stirred tank reactor (CSTR) by reacting sodium hydroxide and silica sand. In the reactor the reaction undergoes liquid-liquid phase, endothermic, with operating temperatures of 220OC and a pressure of 24 bar. To produce sdium silica the process requires raw materials including 3029.54 kgs/hour of sodium hydroxide and 5696.8 kgs/hour of silica sand. The process also needs utilities including 64,394.34 kgs/hour of water, 8,175.9 kgs/hour of steam, 520 liters/hour of fuel diesel, 587.4 kW of electricity obtained from the PLN, and 587.4 kW of generator as backup need 79.01 liters / hour of fuel. Sodium silicate plant with a capacity of 65,000 tons/year. The plant is planned to operate for 330 days/year, and will be established in East Java Gresik Industrial area with a land area of 12,371 m2 and the number of employees is 188 people. The sodium silicate plant require the production costs Rp241,686,040,102.00. The economic analysis of this plant showed a profit before tax of Rp66,338,756,994.00 per year, after tax profits reached Rp49,754,667,745.00 25% per year. The Percent Return On Investment (ROI) before tax 27.4% and 20.6% after taxes. The Pay Out Time (POT) before tax is was 2.67 years and 3.27 years after tax. The Break Even Point (BEP) amounted to 53.6% and the Shut Down Point (SDP) of 28.2%. The Interval rate of return (IRR) accounted for 46.05%. From these analysis economy concluded that the plant is profitable and feasible to set.